Analisa Faktor-faktor CAMEL Terhadap Tingkat Kesehatan Bank Khususnya Bank Perkreditan Rakyat - Lis Sintha (JURNAL MITRA MANAJEMEN, 2013)
UMKM sector resilience against the economic crisis that hit the Republic of Indonesia in 1998 proved that the UMKM sector was less affected by the crisis. It is due to the UMKM sector engaged in almost all sectors such as trade, services, households and others, and can not be denied that UMKM is the economy foundation of a developing country. In this time we can see UMKM development also demands the development of BPR that has the image of fund provider bank for UMKM. With high market demand and a growing number of competitors automatically makes the level of competition becomes more intense especially among rural banks and other non-bank financial institutions, in a super tight competition as well as in a state of high profit oriented rural banks must have sufficient capital, maintaining asset quality well, managed and operated by the precautionary principle, generate enough profit to sustain their business, and to maintain liquidity in order to meet its obligations at all times. In addition, the RB must always meet the various regulations and rules that have been set, which is basically a variety of provisions that refer to the principles of prudence in banking. Assessment of the soundness of banks in Indonesia implemented by Bank Indonesia is largely based on the method of CAMEL (Capital, Asset Quality, Management, Earning, and Liabilities). These five factors are the factors that determine or describe the condition of a bank. If a bank is experiencing problems in one factor or more, the bank is certainly going to have a trouble.Keywords: Capital, Asset Quality, Management, Earning, and Liabilities